Stakeholder Engagement in Pragmatic Clinical Trials: Emphasizing Relationships to Improve Pain Management Delivery and Outcomes. (10th December 2020) - Bastian, Lori A; Cohen, Steven P; Katsovich, Lily; Becker, William C; Brummett, Bradley R; Burgess, Diana J; Crunkhorn, Andrea E; Denneson, Lauren M; Frank, Joseph W; Goertz, Christine; Ilfeld, Brian; Kanzler, Kathryn E; et al.
Abstract: Background: The NIH-DOD-VA Pain Management Collaboratory (PMC) supports 11 pragmatic clinical trials (PCTs) on nonpharmacological approaches to management of pain and co-occurring conditions in U.S. military and veteran health organizations. The Stakeholder Engagement Work Group is supported by a separately funded Coordinating Center and was formed with the goal of developing respectful and productive partnerships that will maximize the ability to generate trustworthy, internally valid findings directly relevant to veterans and military service members with pain, front-line primary care clinicians and health care teams, and health system leaders. The Stakeholder Engagement Work Group provides a forum to promote success of the PCTs in which principal investigators and/or their designees discuss various stakeholder engagement strategies, address challenges, and share experiences. Herein, we communicate features of meaningful stakeholder engagement in the design and implementation of pain management pragmatic trials, across the PMC. Design: Our collective experiences suggest that an optimal stakeholder-engaged research project involves understanding the following: i) Who are research stakeholders in PMC trials? ii) How do investigators ensure that stakeholders represent the interests of a study's target treatment population, including individuals from underrepresented groups?, and iii) How can sustained stakeholder relationships help overcome implementation challenges over the course of a PCT? Summary: Our experiences outline the role of stakeholders in pain research and may inform future pragmatic trial researchers regarding methods to engage stakeholders effectively.